Chemical Toolbox to Decode the Microbiota Lexicon. Issue 14 (30th June 2020) - Qiao, Yuan; Hayashi, Hirohito; Chong Teo, Seng
Abstract: The human microbiota deploys a diverse range of molecules and metabolites to engage in chemical communications with the host, mediating fundamental aspects of host health. Studies of the structures and activities of bioactive molecules produced by the microbiota are imperative to address their implications in microbiota associated diseases in human. By drawing experiences from different research fields, chemists and chemical biologists, who are experts in dealing with chemical molecules, are uniquely positioned to contribute to the emerging knowledge of human microbiota. In this minireview, we discuss the current chemical tools and methods that are pertinent to the discovery of microbiota molecules and metabolites, characterizations of their protein targets, as well as evaluations of their biodistributions in hosts. These are key aspects in understanding the chemical underpinnings of the microbiota‐host interactions that would enable future development of diagnostics and therapeutics targeting the human microbiota. Abstract : The human microbiota encodes a vast repertoire of molecules and metabolites as mediators in the microbiota‐host communications. Chemists and chemical biologists can offer unique perspectives and tools to the explorations of the microbiota‐derived chemical space. Determining the structures and functions of these molecules and metabolites in hosts may contribute to the development of diagnostics and therapeutics for human health.